New benzothiazolium crystals with very large off-diagonal optical nonlinearity - Kim, Seung Jun; Yu, In Cheol; Lee, Ji Ah; Kim, Won Tae; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Rotermund, Fabian; Kwon, O. Pil (Dyes and Pigments, 2021)
In this study, we develop new organic benzothiazolium crystals possessing very large off-diagonal optical nonlinearity. In these crystals, benzothiazolium-based 2-(4-(4-(hydroxymethyl)piperidin-1-yl)styryl)-3-methylbenzothiazol-3-ium (PMB) cations with large molecular optical nonlinearity are incorporated with two anions: 4-(trifluoromethoxy)benzenesulfonate (TFO) with an orthogonal non-planar shape and 5-bromothiophene-2-sulfonate (BTS) with a planar shape. Both PMB-TFO and PMB-BTS crystals exhibit state-of-the-art off-diagonal effective hyperpolarizability (~105 × 10−30 esu) that results from the V-shape and X-shape alignments of PMB chromophores, respectively. Newly developed PMB crystals indicate excellent characteristics for second-order nonlinear optical applications such as difference-frequency generation (e.g. optical rectification) and sum-frequency generation (e.g. second-harmonic generation), which are comparable to current benchmark organic crystals.
Keywords: Benzenesulfonates; Bromothiophenes; Crystal possessing; Non-planar shapes; Optical nonlinearity; Organic crystal; Organics; Planar shape; Sulphonates; THz wave generation; Chromophores; Nonlinear optics; Organic crystals; THz wave generation